X‐Ray Exposure in Cardiac Electrophysiology: A Retrospective Analysis in 8150 Patients Over 7 Years of Activity in a Modern, Large‐Volume Laboratory. Issue 11 (21 September 0207) - Casella, Michela; Dello Russo, Antonio; Russo, Eleonora; Catto, Valentina; Pizzamiglio, Francesca; Zucchetti, Martina; Majocchi, Benedetta; Riva, Stefania; Vettor, Giulia; Dessanai, Maria Antonietta; Fassini, Gaetano; Moltrasio, Massimo; et al.
Abstract : Background: Only a few studies have systematically evaluated fluoroscopy data of electrophysiological and device implantation procedures. Aims of this study were to quantify ionizing radiation exposure for electrophysiological/device implantation procedures in a large series of patients and to analyze the x‐ray exposure trend over years and radiation exposure in patients undergoing atrial fibrillation ablation considering different technical aspects. Methods and Results: We performed a retrospective analysis of all electrophysiological/device implantation procedures performed during the past 7 years in a modern, large‐volume laboratory. We reported complete fluoroscopy data on 8150 electrophysiological/device implantation procedures (6095 electrophysiological and 2055 device implantation procedures); for each type of procedure, effective dose and lifetime attributable risk of cancer incidence and mortality were calculated. Over the 7‐year period, we observed a significant trend reduction in fluoroscopy time, dose area product, and effective dose for all electrophysiological procedures ( P <0.001) and a not statistically significant trend reduction for device implantation procedures. Analyzing 2416 atrial fibrillation ablations, we observed a significant variability of fluoroscopy time, dose area product and effective dose among 7 different experienced operators ( P <0.0001) and a significant reduction of fluoroscopy use over time ( P <0.0001) for all of them. Considering atrial fibrillation ablation techniques, fluoroscopy time was not different ( P = 0.74) for radiofrequency catheter ablation in comparison with cryoablation, though cryoablation was still associated with higher dose area product and effective dose values ( P <0.001). Conclusions: Electrophysiological procedures involve a nonnegligible x‐ray use, leading to an increased risk of malignancy. Awareness of radiation‐related risk, together with technological advances, can successfully optimize fluoroscopy use.